Deteksi Audit Kepatuhan : Sistem Informasi Akuntansi Penerimaan Uang Pada Bisnis Café Melalui Pengendalian Internal - Nur Faiza Mas’udiyah; Argaleka Ayu Candraningsih; Tri Ratnawati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This research aims to analyze the detection and internal control applied in the revenue accounting information system of a café business, as well as the importance of compliance auditing in maintaining the reliability and accuracy of financial data. A good accounting information system is an essential component in managing the revenue of a café business. Effective detection and internal control are highly needed to prevent and detect fraud or errors that may occur in the revenue collection process. This research utilizes a qualitative method with a case study approach on a café business. Data is collected through interviews with café management, direct observation, and analysis of documents related to the revenue accounting information system. The research findings indicate that the café business has implemented several steps of detection and internal control, including task segregation, document verification, the use of automated systems, and periodic reconciliations.